An analysis of eco-sensitive hotel guest room experience and its impact on room selection recommendation. (10th April 2019) - Sudhagar, D.P.
The purpose of the study is to analyse the eco-sensitive hotel guest room experience and its impact on room selection recommendation. Room tips reviews of an eco-sensitive hotel featuring in TripAdvisor were taken for content analysis. The study result indicates that majority of guest provided positive feedback on the rooms they had stayed. Predominantly, location was mentioned as an important attribute to be considered while selecting a room for a stay followed by the view of the room. Findings also indicate that the comfort of the room, windows of the room, room category, room plan, room amenities, quality of air-conditioning, and quietness of the room are the other factors impact the stay experience. Attributes such as lightning of the room, noise, service quality, room size, and layout were less frequently cited. Surprisingly, there was no review reported about eco-sensitive feature provided in the hotel. The room attributes play a significant role in decision-making behaviour of the guest.